Lung cancer resection with concurrent off-pump coronary artery bypasses: safety and efficiency - Ma, Xuchen; Huang, Fangjiong; Zhang, Zhitai; Song, Feiqiang; Ou, Songlei (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: To assess the safety and efficacy of combined surgery for patients with concurrent lung cancer and severe coronary heart disease (CHD). Methods: Between 2003 and 2014, 34 patients with stage I or II lung cancer and simultaneous severe CHD underwent combined off-pump coronary artery bypass (OPCAB) grafting and lung resection. Surgically, myocardial revascularization was performed first and followed by lobectomies through the same or a second incision. Video-assisted thoracoscopes were used in some cases. Five patients also received chemotherapy before or after combined surgery in an effort to improve the long-term survival. Results: All patients survived the operation and no new myocardial infarctions (MIs) occurred in the perioperative period. The most frequent complications were cardiac arrhythmias (5 cases), atelectasis (4 cases), and pulmonary infections (2 cases). All patients were followed up for 5–60 months. Within this period, 6 patients (17.6%) died due to cancer recurrence. The 3- and 5-year survivals were 75% and 67% for these lung cancer patients, respectively. Conclusions: Combined OPCAB and pulmonary resection for early stage lung cancer patients with concurrent severe CHD is a relatively safe and effective treatment with satisfactory long-term survival rates, especially for those patients with three-vessel disease who are not usually candidates for percutaneous coronary intervention (PCI) before open surgery.